Abnormal bone remodelling activity of dental follicle cells from a cleidocranial dysplasia patient. (8th June 2018) - Liu, Yang; Zhang, Xianli; Sun, Xiangyu; Wang, Xiaozhe; Zhang, Chenying; Zheng, Shuguo
Abstract : Objectives: To explore the role of dental follicle cells (DFCs) with a novel cleidocranial dysplasia (CCD) causative gene RUNX2 mutation (DFCs RUNX 2+/m ) in delayed permanent tooth eruption. Materials and methods: A CCD patient with typical clinical features was involved in this study. DFCs RUNX 2+/m were cultured and DNA was extracted for RUNX2 mutation screening. Measurements of cell proliferation, alkaline phosphatase (ALP) activity, alizarin red staining and osteoblast‐specific genes expression were performed to assess osteogenesis of DFCs RUNX 2+/m . Co‐culture of DFCs and peripheral blood mononuclear cells (PBMCs), followed tartrate‐resistant acid phosphatase (TRAP) staining, real‐time PCR and western blot were performed to evaluate osteoclast‐inductive capacity of DFCs RUNX 2+/m . Results: A missense RUNX2 mutation (c. 557G>C) was found in DFCs RUNX 2+/m from the CCD patient. Compared with normal controls, this mutation did not affect the proliferation of DFCs RUNX 2+/m, but down‐regulated the expression of osteogenesis‐related genes, leading to a decrease in ALP activity and mineralisation. Co‐culture results showed that DFCs RUNX 2+/m reduced the formation of TRAP + multinucleated cells and the expression of osteoclastogenesis‐associated genes. Furthermore, the mutation reduced the ratio of RANKL/OPG in DFCs RUNX 2+/m . Conclusions: DFCs RUNX 2+/m disturbs bone remodelling activity during tooth eruption through RANK/RANKL/OPG signalling pathway and may thus be responsible for impaired permanent tooth eruption in CCD patients.